Siri Fails the Turing Test: Computation, Biosemiosis, and Artificial Life - Alexander, Victoria (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2019)
Artificial Intelligence (AI) designers try to mimic human brain capabilities with “self-learning” neural networks trained by selection processes. Yet decades on, AI still fails the Turing Test. While computers use codes and develop algorithms apart from contexts, living cells use signs and develop semiotic habits within contexts. This difference, I argue, is partly due to the collective activities of biological neurons that produce traveling waves, which, in turn, further constrain neural activity. It appears wave patterns function as contexts shaping the content of the local connections. At the time of his death, Alan Turing was investigating the organizing role of emergent wave patterns on biological development. Had he lived to continue this work, he might have reoriented AI research, which instead has become merely a tool for stereotyping and regularizing, not thinking.